2002
DOI: 10.1001/archsurg.137.11.1243
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Surgery in the Geriatric Patient

Abstract: Background: Although age itself is no contraindication for major surgical procedures, few patients 75 years and older undergo thyroid surgery. Hypothesis: Thyroid surgery in the geriatric patient can be performed with low morbidity and mortality. Design: Retrospective analysis of prospectively documented data. Setting: University hospital referral center. Patients: We included 738 patients undergoing thyroid surgery within 5 years, of whom 55 (7.5%) were 75 years or older (group 1) (mean±SD age, 79.9±4.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 30 publications
8
84
6
1
Order By: Relevance
“…18,20 Although some studies reported higher frequency of MTC in patients older than 75 years others reported no difference. 12,[20][21][22][23] Likely, authors did not find any difference in MTC between geriatric and nongeriatric patients in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…18,20 Although some studies reported higher frequency of MTC in patients older than 75 years others reported no difference. 12,[20][21][22][23] Likely, authors did not find any difference in MTC between geriatric and nongeriatric patients in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…While most studies (Christian Passler et al, 1 Melanie W. Seybt et al, 3 Michael C. Sullivan et al, 4 Ríos A et al 5 and Rodríguez et al 6 ) found that there is no greater risk for thyroid surgery in the elderly. One study (Mekel et al) 7 found a higher increase in morbidity in older group.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard definition for geriatric age group 1 . WHO defines the geriatric age group as the age above 60 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, few papers have reported thyroid operation outcomes for patients with severe systemic disease [2][3][4]. The American Society of Anesthesiologists Physical Status (ASA-PS) classification system is a method of characterizing patient operative risk, and it is performed by anesthesiologists before every procedure in which a patient will undergo anesthesia.…”
mentioning
confidence: 99%